Dampak Thin Capitalization, Profitabilitas, Dan Ukuran Perusahaan Terhadap Tindakan Penghindaran Pajak - Tesa Anggraeni; Rachmawati Meita Oktaviani (ITB AAS INDONESIA, 2021)
This researcher examines how thin capitalization, profitability, and company size affect tax avoidance. The sample used is manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 to 2019. The sampling method uses purposive sampling in order to obtain 69 manufacturing companies. This study uses panel data regression analysis techniques with the help of the Eviews 10. This study shows that the independent variable thin capitalization has no effect on tax avoidance. While profitability has a significant positive effect on tax avoidance, and company size has a significant negative effect on tax avoidance.